1. The problem statement, all variables and given/known data This is just a simple proof of substitution, but after one day struggle, I still can't get where that minus sign appear. 2. Relevant equations Here is the equation: $$ (p_1 - p_3)^2=-(\mathbf p_1 - \mathbf p_3)^2$$ where ##p_1=(E/c,\mathbf p_1)## and ##p_3=(E/c, \mathbf p_3)## is four-momentum of incident and scattered electron respectively, with stationary target. 3. The attempt at a solution Here is my doodling: $$ (p_1 - p_3)^2=(E/c+\mathbf p_1-E/c-\mathbf p_3)^2=(\mathbf p_1 - \mathbf p_3)^2. $$ Which step that I miss?